Enhancing the Quality of Education through Innovative Educational Practices at Kalidawir Public Elementary School - Satunggale Kurniawan; Rahman, Muhammad Afifi (Yayasan Cendekiawan Indonesia Timur, 2025)
Study This aiming For increase quality education at Kalidawir Elementary School through implementation practice education innovative. Background study This is low quality learning consequence domination method conventional which focuses on memorization and theory. For answer challenge said, the approach innovative like learning based on project, integration technology, and methods collaborative applied in the learning process. Research This use approach qualitative with method observation, interviews, and documentation For dig understanding deep to implementation and impact from practice innovative in class. Research results show that education innovative in a way significant increase involvement students, results Study academic, as well as skills social and collaborative they. Learning based on project make student more active and contextual in understand material. While integration technology strengthen interest learn and enrich experience learn. However Thus, the limitations means infrastructure as well as lack of teacher competence in utilise technology Still become obstacle main. In overall, research This show that practice education innovative can be an effective strategy For increase quality learning at school Basic. Success implementation is highly dependent on support teacher training, provision infrastructure adequate, and involvement all over element school. Findings This expected become reference in development policy education adaptive basis​ to development of the times and needs student.